Climate change and mental illness: Another pandemic post coronavirus disease 2019? - Rijal, Rika (Journal of Kathmandu Medical College, 2023)
The emergence of coronavirus disease 2019 (COVID-19) as a pandemic was a stressful situation for all of us. With the limitation of social contact and shift in our work modality, many things changed and it became the new normal. While some found opportunities even in such situation, many became crippled to another silent pandemic of mental illness. After the widespread use of vaccine, things have started to return to normal, or have they?